Conservation issues of large rolled paintings on the Portuguese altarpieces - Rita Macedo Moreira (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This article focuses on the study of the historical context and the conservation issues of large rolled paintings on the Portuguese altarpieces of the 18th to 20th centuries, emphasizing their originality and dynamism. Widely used in Portugal, this type of painting is exposed during a specific period of time of the liturgical year and, depending on scenic claims, is presented or simply stored through the system that moves it. This particularity originates characteristic degradation processes as well as very specific needs of exhibition.